Profaning Bodies / Profaning Nations. On La emancipada[The Emancipated One] as Foundational Novel in Ecuadorian Literature - Marín Lara, Karina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This work aims at providing an alternative reading about what we can understand as representation of the body , in order to question notions such as foundational fiction and national literature. My goal is to formulate other ways to examine images of the body that have remained under the rubble in the effort to construct a history of literature, specifically Ecuadorian literary history. Taking into account the first Ecuadorian novel, La emancipada (1863), written by Miguel Riofrío, I suggest: if Rosaura’s dead body, described as a putrefied body, cannot exhibit a respectable appearance, how can we understand this body mas the starting point for the consolidation of a literary corpus ? How can a national literary history be possible, when it is constructed over the representation of this dismembered and unviable body image?